Assessing reading 2 : changing practice in classrooms : international perspectives on reading assessment - Coles, Martin, 1952-; Jenkins, Rhonda (Routledge, 1998)
This book focuses directly on the classroom, on the challenges individual teachers face in classroom-based assessment, and how these challenges have been and are being met in a range of international contexts.